The BCC-FCC Structural Phase Transition in Semimetal Systems - Lam, Nguyen The (VNU Journal of Science: Mathematics - Physics; Vol 31 No 3, 2015)
It will show that, the second structural phase transition (BCC-FCC) may be took place in the semimetals cause of extra condition as temperature or doping… The first structural phase transition occurs is due to nesting vector Q = p. The free energy of system in some crystal structures are depended on temperature and doping. In this case, the temperatiure or doping is increased, the free energy of system in this crystal structure is lower than itself in other crystal structure. So the second structural phase transition may be occurred. Keyword: BBC-FCC transition, structure phase transaction.